AB1325 HAND FUNCTION IS IMPAIRED IN PATIENTS WITH RHEUMATOID ARTHRITIS, PSORIATIC ARTHRITIS, AND PSORIASIS COMPARED TO HEALTHY CONTROLS. (June 2019) - Liphardt, Anna-Maria; Liehr, Sonja; Manger, Eva; Bieniek, Lisa; Kleyer, Arnd; Simon, David; Tascilar, Koray; Sticherling, Michael; Rech, Jürgen; Schett, Georg; Hueber, Axel
Abstract : Background: Inflammatory-rheumatic diseases affect hand joints with swelling and pain, leading to joint destruction. Even patients with psoriasis only may suffer subclinical inflammation in the hand joints, leading to changes of bone [1]. Finger joint involvement is different for rheumatoid arthritis (RA), psoriatic arthritis (PsA) and psoriasis (Pso) but hand function in these patients is not well characterized. Objectives: To quantify and compare grip strength and hand function in patients with RA, PsA and Pso and to relate these outcomes to disease activity. Methods: Patient diagnosed with RA (ACR/EULAR 2010), PsA (Caspar) and Pso and 54 healthy individuals were included in the study after written informed consent. Maximal isometric grip strength (kPA) was measured with a hand dynamometer (Lafayette Instrument, Lafayette, IN, USA) as the highest value out of three measurements. Hand function was determined by way of the Moberg Picking-Up Test (MPUT) and the fastest (s) of two measurements was used. Disease activity was calculated as DAS28_ESR and TJC/SJC 78/76 was recorded. One-way Analysis of Variance (ANOVA), factorial ANOVA and Games-Howell post-hoc testing was performed (p<0.05). Results: 101 RA (63 f; 38 m; age: 59.1±13.2 yrs), 92 PsA (48 f, 44 m; age 54.8±11.6 yrs) and 51 Pso patients (19 f, 32 m; age 47.3±14.1 yrs), as well as 54 healthy control subjects (30 f, 24 m; age 54.6± 16.5 yrs) participated in the study. Disease duration (yrs) was not different between groups (RA: 11.03±10.1, PsA: 9.1±9.75, Pso: 12.5±11.7; p=0.156) but Pso patients in our cohort were younger compared to RA and PsA patients. Mean DAS28_ESR was < 3.2 for all patient groups with control subjects (DAS28 1.6 ± 0.7) having lower scores compared to all patient groups and Pso patients presenting with lower DAS28 (2.3±1.3) compared to RA (3.0±1.3) and PsA (2.9±1.3). While TJC was higher for all patients compared to controls (RA: 5.2±6.8, PsA: 5.9±8.1 Pso: 3.2±6.4; CON: 0.5±1.4; p=0.00), SJC was higher for RA and PsA compared to Pso and CON (RA: 0.7±1.0, PsA: 0.9±2.2 Pso: 0.1±0.3; CON: 0.5±1.4; p=0.000). Grip strength of the dominant and/or affected hand of RA patients was lower compared to PsA, Pso and CON (Figure 1A ). In contrast to this, hand function of the same hand in all tested patient groups was reduced compared to CON (Figure 1B ). The results for grip strength and hand function were not different for the dominant and the affected hand and are independent of age differences between groups. Conclusion: Overall, RA patients showed significantly lower grip strength compared to PsA and Pso patients as well as to the control group, whereas all three patient groups performed worse in the MPUT compared to the control cohort. This suggests that grip strength may be preserved longer than hand function in patients with inflammatory rheumatic disease. Further, it was surprizing that hand function was reduced in Pso patients without arthritic correlate compared to healthy subjects. This suggests that hand function may provide a potential parameter for discriminating Pso patients at risk for subclinical joint involvement. This study was funded by research support from Novartis Pharma, GmbH. References: [1] Faustini F, Simon D, et al. 2016, Ann Rheum Dis 75: 2068-2074. Disclosure of Interests: Anna-Maria Liphardt Grant/research support from: Novartis Pharma GmbH, Sonja Liehr: None declared, Eva Manger: None declared, Lisa Bieniek: None declared, Arnd Kleyer Grant/research support from: Lilly, Consultant for: Lilly, Speakers bureau: Abbvie, David Simon Grant/research support from: Novartis, Consultant for: Lilly, Speakers bureau: Janssen, Koray Tascilar: None declared, Michael Sticherling: None declared, Jürgen Rech Grant/research support from: Bristol-Myers Squibb and Celgene (greater than 10, 000), Consultant for: Bristol-Myers Squibb, Celgene, Chugai, GlaxoSmithKline, Janssen, Eli Lilly, Novartis, Roche, Sanofi Aventis, and UCB (in total more than 10, 000), Speakers bureau: Bristol-Myers Squibb, Celgene, Chugai, GlaxoSmithKline, Janssen, Eli Lilly, Novartis, Roche, Sanofi Aventis, and UCB (in total more than 10, 000), Georg Schett: None declared, Axel Hueber Grant/research support from: Novartis, Pfizer, Consultant for: Lilly, Speakers bureau: Lilly, Novartis, Janssen, Abbvie